In Vivo assessment of antigen-monoclonal antibody by radioimmuno scintigraphy - Glait, H. M.; Horestein, A. L.; Koss, Amalia; Sliak, E.; D’ Orio, E.; Olivari, A. J. (Centro Oncológico de Medicina Nuclear; Argentina, 1986)
Fil: Glait, H. M. Comisión Nacional de Energía Atómica; Argentina